If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(5+2x)-5=3(3x+7)=
We move all terms to the left:
4(5+2x)-5-(3(3x+7))=0
We add all the numbers together, and all the variables
4(2x+5)-(3(3x+7))-5=0
We multiply parentheses
8x-(3(3x+7))+20-5=0
We calculate terms in parentheses: -(3(3x+7)), so:We add all the numbers together, and all the variables
3(3x+7)
We multiply parentheses
9x+21
Back to the equation:
-(9x+21)
8x-(9x+21)+15=0
We get rid of parentheses
8x-9x-21+15=0
We add all the numbers together, and all the variables
-1x-6=0
We move all terms containing x to the left, all other terms to the right
-x=6
x=6/-1
x=-6
| 0.6x+1=-0.2x+3.2 | | 3(x-5)-5x=-15-2x | | X+3x/4=12 | | 45=x^2-36 | | 3/5x+8=2/5x+7 | | F(5)=3x^2+2x-2 | | 35=v-8v | | x+9=96 | | 1/2x+x+x+1/2x=180 | | -2-2/3w=10 | | 1/2m-9=4 | | 2x+6=-1x+5 | | 12=16k/3 | | 4x=2=14 | | -6x-6+x=9 | | -7(x+9)=(x-5)-14x | | 4(x+15)=9 | | 3(5x-2)=-3(x+16) | | -3x+21+2=20 | | 3h/10-17=527/40 | | 32-1(3c+4)=2(c+5)+c | | 5x-2+3=x | | 4(x+3)=-2(x-5) | | 5y−4=36 | | 11b–20=2+10b–3 | | -5x+7=-2(x-4) | | -x+1=x+21 | | 3x-10(2x-1)=44 | | y+3y=96= | | 4y-12+3y+18=27 | | -2/3=-4/3(s-1/3) | | y+3y=86 |